Peran Status Gizi Terhadap Tingkat Kecerdasan Kognitif Anak - Mufia Muin; Nurfardiansyah Burhanuddin; Zulfahmidah Zulfahmidah; Windy Nurul Aisyah Aisyah (Yayasan Citra Cendekia Celebes, 2020)
Background and Objectives: Nutritional status is important role in the metabolism of the body and in the process of thinking or reasoning a role in thinking processes, concentration power and related to learning efficiency. With good nutritional condition is expected to have an impact on good learning achievement. Methods: The source of this research data comes from the literature obtained through the internet is the result of research from national or international journals in 2010-2020. Results: There are studies that explain malnutrition or obesity impact on a child's cognitive delay and good nutritional status will have an impact on the cognitive improvement of the child. But optimal cognitive development is not enough just with good nutritional status, it takes good stimulus efforts. Conclusion: Nutritional status is important for cognitive development in children.